L’autobiografia e il racconto del trauma: a partire da Parole soffocate di S. Kofman - Ponzio, Julia (Rivista Italiana di Filosofia del Linguaggio, 2020)
In Paroles suffoquées, published in 1987, Sarah Kofman addresses the issue of how to tell a trauma starting from the loss of her father, deported to Auschwitz. The question of the relationship between language and emotions becomes, in Kofman’s text, the tension between the duty of the witnesses and the difficulty of finding the words to tell a painful event. Paroles suffoquées starts with a quote from Le pas au delà, in which Blanchot describes the event of the Shoah as an interruption of history. This interruption of history is also a lack of the words necessary to tell the pain. Kofman wonders how to find this suffocated word to narrate the trauma. To find the suffocated words is necessary not only to ask how to tell, but also to question the meaning of this tale, the relationship between language and history, and the space of autobiography within this relationship. In this paper, I try to show how Kofman, in Paroles suffoquées, through a constant dialogue with Nietzsche, Blanchot and Derrida comes to the idea of ​​a language without reference in which the suffocated word begins to resonate not as meaningful but as voice.